1998
DOI: 10.1007/s004680050144
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between respiration and dormancy in buds of three hardwood species with different chilling requirements for dormancy release

Abstract: AbstractmRespiration in vegetative buds of mature Betula pendula, Alnus glutinosa and Prunus padus trees was measured monthly at 15°C from mid-October 1996 to natural outdoor budburst in April 1997. In B. pendula the effect of bud water content on respiration was also estimated (December±April) by artificial imbibition of buds for 24 h prior to measurement of respiration. For estimation of corresponding bud dormancy status, batches of twigs were forced at identical monthly intervals at 15°C in long days (24 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…1). Similar results were obtained for Betula pendula, Alnus glutinosa, and Prunus padus [17]. On the branches of A. glutinosa placed in a controlled-climate chamber in November, the buds unfolded in 60 days, in March, they unfolded as early as in 10 days; the buds of P. padus opened in 25 and 5 days, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…1). Similar results were obtained for Betula pendula, Alnus glutinosa, and Prunus padus [17]. On the branches of A. glutinosa placed in a controlled-climate chamber in November, the buds unfolded in 60 days, in March, they unfolded as early as in 10 days; the buds of P. padus opened in 25 and 5 days, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Low-temperature exposure of a certain duration is necessary for the buds of woody plants in the temperate zone. It prevents early initiation of growth in spring and shoot injury in case of return of cold weather [17]. Our investigations showed that a disturbance of biological rhythm of development as a result of artificial breaking of bud dormancy exerted a profound influence on the initial stage of extra-bud growth of bilberry shoots.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…3.12b) measures the increasing rate of ontogenetic development towards bud burst obtained with progressively longer durations of chilling. This rate, too, often evinces withinpopulation variation, but such variation is manifested as deviation from the mean DBB observed at any given duration of chilling rather than in the form of the DBB curve (Myking 1998). This variation is not shown in Fig.…”
Section: Experimental Studiesmentioning
confidence: 97%